Pengaruh Pajanan Toluena Terhadap Gambaran Sel Spermatogonia A Rattus Strain Wistar - Muchtaruddin Mansyur; Pudji Sari; Dwi Anita Suryandari; Muhammad Ilyas Iqbal; Pramudianto Pramudianto (PENGURUS BESAR IKATAN DOKTER INDONESIA (PB IDI), 2021)
Intoduction: Acute and chronic exposure to toluene at high doses is known to affect all organs of the body including the spermatogenesis process. In the industrial sector, the use of toluene as a solvent is still widely used, up to 10 million tons per year. The control over health problems that may occur is carried out by applying work exposure threshold values. This research aims to explore the effect of toluene exposure at the threshold value range on spermatogenesis.Method: This research used laboratory experiment on 30 male Wistar rats which were divided into five groups of different exposure levels, namely 12.5 parts per million (ppm], 25 ppm, 50 ppm, 100 ppm, and no exposure (control). Exposure was given for 4 hours daily over 14 days through a hood with measured release in the glass cage. The toluene exposure markers observed were Malondialdehyde (MDA) in the blood tissue and testicles using the Thiobarbituric Acid Reactive Substances (TBARS) method. The effect on the spermatogenicity process was assessed by counting the spermatogonia A cells of male Wistar rats with Periodic Acid Schiff (PAS) staining and is calculated by the Abercrombie formula. Analysis of the correlation between the level of exposure and its effect on the increase in malondialdehyde, and spermatogenesis was carried out using the Spearman correlation analysis.Result: There was a moderately positive correlation between levels of toluene exposure and plasma MDA levels (r = 0.42; p = 0.025). Meanwhile, on [the issue of] the quantity of spermatogonia cells, a high level of negative correlation with exposure levels was obtained (r = -0.68; p = 0.001).Conclusion: Toluene exposure in male Wistar rats within the range of threshold values influenced the increase in plasma MDA levels and decreased the Spermatogenia A cells. However, toluene exposure did not affect the testicular MDA levels of male Wistar rats.